Transition Metal Catalysis for the Asymmetric Synthesis of 2-Arylethylamines: A Review of the New Millennium - Alejandro Manchado; Ángel García-González; Carlos T. Nieto; Nieves G. Ledesma; David Díez; Narciso M. Garrido (Molecules)
The 2-arylethylamine motif is very well-known in medicinal chemistry because of its interesting properties when it comes to interacting with the Central Neural System thanks to its ability to pass the blood–brain barrier. This nitrogen-containing family of compounds is of great interest in synthetic organic chemistry and, when it comes to its asymmetric synthesis, great challenges can be faced in order to obtain the chiral purity required in the drug industry. Thus, we provide a concise transition metal review presenting the recent advances in the synthesis of chiral 2-arylethylamines using transition metals as the main catalysts in the introduction of chirality. Both conventional and photocatalysis methods will be covered, considering the main transition metal used in the studies.